Preparation and photophysical properties of thin films of coumarin dyes - Ibrayev, N.Kh.; Seliverstova, E.V.; Alekseeva, V.I.; Marinina, L.E.; Savvina, L.P. (Springer, 2013)
The results from investigating the photophysical properties of new coumarin dyes synthesized and incorporated into Langmuir–Blodgett films are presented. A method for forming monolayers on the surface of a water/air interface is proposed. The phase states of mixed monolayers on a water surface are studied. It is found that mixed monolayers of amphiphilic polyampholyte and dye allow us to obtain more stable and condensed films, relative to films of single components. The spectral and luminescent properties of synthe sized dyes in solution and in Langmuir–Blodgett films are studied
Keywords: coumarin dyes; properties; Langmuir–Blodgett films